Bacis clinical parasitology - Neva, Franklin A.; Brown, Harold W. (Appleton & Lange, 1994)
This work emphasizes the clinical aspects of parasitology, such as the pathology, symptomology, diagnosis, treatment and prevention. Coverage of morphologic and biologic characteristics of the various parasites have been restricted to those features essential for their diagnosis. New material is included in this edition on AIDS and more effective drugs and treatments for parasitic infections. The book is intended for medical students, laboratory technicians, teachers and students of microbiology, practising physicians and infectious disease specialists